Assessing peat surface motion using Interferometric Synthetic Aperture Radar (InSAR) in the Great Fen area of Cambridgeshire, UK - Patil, Abhishek; Khouakhi, Abdou; Girkin, Nicholas T.; Holman, Ian P. (Elsevier, 2026)
Peatland degradation is a critical global climate issue, releasing millions of tonnes of CO2 annually due to drainage and changes in land use. As countries strive to meet net-zero targets, restoring degraded peatlands has become a priority for carbon sequestration and biodiversity conservation. However, monitoring peatland recovery remains a challenge, especially for large-scale restoration projects. This research is driven by the need for low-cost validation of peatland re-wetting schemes, enabling robust monitoring of peat physical condition and hydrological recovery, with implications for carbon accounting and agriculture’s contribution to net-zero targets. This study addresses this gap by applying remote sensing data from Interferometric Synthetic Aperture Radar (InSAR) to track peat surface motion in Cambridgeshire's Great Fen, one of the UK’s largest lowland peatland restoration initiatives. Sentinel-1 InSAR data (2015–2025) were used to quantify ground motion and derive deformation-based proxies for peat carbon flux. Our analysis revealed distinct subsidence patterns for undrained, early-restored, and later-restored farms, enabling first-order, deformation-based carbon flux estimation under common parameter assumptions. Early-restored farms experienced subsidence rates of up to 1.17 cm/year and deformation-associated carbon flux proxies of 14.50 tons CO2/ha/year, compared to 1.40 cm/year and 17.37 tons CO2/ha/year in later-restored sites. National Nature Reserves (Holme Fen and Woodwalton), which remained undrained, recorded the lowest subsidence (∼0.48 cm/year) and lowest deformation-associated carbon loss proxy (5.98 tons CO2/ha/year), linked to restoration timelines and peat moisture regimes. These estimates, interpreted as relative indicators rather than direct measurements of net ecosystem carbon balance, demonstrate InSAR’s utility for tracking peatland condition and relative peat carbon vulnerability across restoration timelines. Seasonal fluctuations aligned with soil moisture and precipitation anomalies, indicating a strong hydrological control on peat surface motion. Together, these findings show that InSAR provides a high-resolution, cost-effective tool for continuous monitoring of peatland physical dynamics, supporting comparative assessment of restoration outcomes and climate-relevant land management decisions.
Keywords: 37 Earth Sciences; 44 Human Society; 15 Life on Land; 3709 Physical geography and environmental geoscience; 4406 Human geography; Interferometric Synthetic Aperture Radar (InSAR); Sentinel-1; Carbon sequestration; Great Fen Peatland; Carbon market funding; Re-wetting schemes; Net zero; National nature reserve